AMERICAN LITERATURE. THE DIFFERENCES BETWEEN LITERATURE OF THE NORTH AND THE SOUTH (International Educators Conference, 2025)
This article examines the distinct features of American literature from the North and the South, highlighting the historical, cultural, and ideological contexts that shaped their themes, styles, and characters. By analyzing representative works, the study reveals how northern literature emphasized industrial progress, social reform, and intellectual inquiry, while southern literature centered on tradition, agrarian life, and the moral complexities of slavery. Through comparative analysis, the research underscores the importance of regional identity in the development of American literary traditions.